Near Infrared Spectroscopy Study of the Frontopolar Hemodynamic Response and Depressive Mood in Children with Major Depressive Disorder: A Pilot Study - Usami, Masahide (Public Library of Science, 2014)
AIM: The aim of this study was to evaluate the frontopolar hemodynamic response and depressive mood in children with mild or moderate major depressive disorder during six weeks treatment without medication. METHODS: The subjects were 10 patients with mild or moderate depression. They were depressive drug-naive children and adolescents. The scores of Depression Self Rating Scale (DSRS), the results of the Verbal Fluency Test (VFT), and the concentrations of oxy-hemoglobin (Oxy-Hb) of frontal pole brain assessed by two-channel near infrared spectroscopy (NIRS) after six weeks of treatment was compared with those of initial treatment. RESULTS: The score of DSRS was significantly reduced after six weeks of initial treatment (p<0.001, t-test). The word number of VFT was not significantly changed after six weeks of treatment. The oxy-Hb concentration significantly increased after six weeks of treatment (p<0.001, t-test). CONCLUSIONS: This study demonstrated that the concentration of oxy-Hb of frontopolar cortex in children with mild and moderate depression improved along with their depressive mood. These results suggested that concentration of oxy-Hb using NIRS may be used as the state maker for change in depressive mood of children having depression, similar to that in adults.